2017
DOI: 10.1002/hed.25040
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor volume in patients with head and neck squamous cell carcinoma treated with primary surgery

Abstract: The tumor volume had an impact on CR, OS, and clear margins. The tumor volume may also aid in selecting HNSCC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
3
14
0
2
Order By: Relevance
“…In planning CTs of the same patients 3–4 weeks later, mean PT-volume was approximately 25 mL (median≈17 mL; table 2). These PT-volumes are in line with previous publications reporting mean volumes of 11–37 mL 23–26. Mean LN-volume measured in diagnostic CTs was 9 mL (median≈2 mL) and approximately 15 mL (median≈4 mL) in planning CTs (table 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In planning CTs of the same patients 3–4 weeks later, mean PT-volume was approximately 25 mL (median≈17 mL; table 2). These PT-volumes are in line with previous publications reporting mean volumes of 11–37 mL 23–26. Mean LN-volume measured in diagnostic CTs was 9 mL (median≈2 mL) and approximately 15 mL (median≈4 mL) in planning CTs (table 2).…”
Section: Discussionsupporting
confidence: 91%
“…The development of the research question was based on previous publications exploring tumour volume in HNSCC15 and its prognostic value if treated primarily with surgery 23. Neither patients nor the public were involved in the design of the study, the recruitment of the study or the conduct of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour volume is a well-established and benchmarked prognostic factor for lung and head and neck cancers [5,11]. Therefore, correctly identifying if a feature or a combination of feature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Knegjens studied 360 patients undergoing primary chemoradiotherapy for head and neck cancer and found a 14% increased hazard ratio for local recurrence per 10 cm 3 increase in TV 37 . Dejaco et al measured TV in 125 patients undergoing surgical resection for head and neck cancer, and found that volume was predictive of worse OS 28 …”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of primary tumor volume (TV) in predicting disease progression and survival has been reported in other head and neck cancers, 28 but not in SNMM. Our objective was to define the relationship between TV and the risk of distant metastases and OS in patients with SNMM.…”
Section: Introductionmentioning
confidence: 99%